Genome-edited crops for improved food security of smallholder farmers - Pixley, Kevin V.; Falck-Zepeda, Jose B.; Paarlberg, Robert L.; Phillips, Peter W. B.; Slamet-Loedin, Inez H.; Dhugga, Kanwarpal S.; Campos, Hugo; Gutterson, Neal (Nature genetics, 2022)
Widespread enthusiasm about potential contributions of genome-edited crops to address climate change, food security, nutrition and health, environmental sustainability and diversification of agriculture is dampened by concerns about the associated risks. Analysis of the top seven risks of genome-edited crops finds that the scientific risks are comparable to those of accepted, past and current breeding methods, but failure to address regulatory, legal and trade framework, and the granting of social license, squanders the potential benefits.